1999
DOI: 10.1523/jneurosci.19-08-03023.1999
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor Expression Regulates Quantal Size and Quantal Content at theDrosophilaNeuromuscular Junction

Abstract: At the Drosophila glutamatergic neuromuscular junction, the postsynaptic cell can regulate synaptic strength by both changing its sensitivity to neurotransmitter and generating a retrograde signal that regulates presynaptic transmitter release. To investigate the molecular mechanisms underlying these forms of plasticity, we have undertaken a genetic analysis of two postsynaptic glutamate receptors that are expressed at this synapse. Deletion of both genes results in embryonic lethality that can be rescued by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
410
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(455 citation statements)
references
References 50 publications
(73 reference statements)
42
410
2
1
Order By: Relevance
“…The frequency of spontaneous synaptic potentials (similar to vertebrate miniature end-plate potentials) is a widely used measure of synaptic function (11,(47)(48)(49)(50)(51) and scales with membrane excitability. Elevated spontaneous release is also characteristic of other activity mutants with reduced K ϩ currents (46).…”
Section: Sdn Expression Enhances Neuronal Excitabilitymentioning
confidence: 99%
“…The frequency of spontaneous synaptic potentials (similar to vertebrate miniature end-plate potentials) is a widely used measure of synaptic function (11,(47)(48)(49)(50)(51) and scales with membrane excitability. Elevated spontaneous release is also characteristic of other activity mutants with reduced K ϩ currents (46).…”
Section: Sdn Expression Enhances Neuronal Excitabilitymentioning
confidence: 99%
“…Also, in the mollusc Helisoma, acquisition of excitation-secretion machinery at nerve-muscle synapses involves activity-dependent signaling through the postsynaptic receptors (Poyer and Zoran, 1996). Finally, at Drosophila neuromuscular synapses, the postsynaptic glutamate receptor regulates quantal size and quantal content of developing presynaptic terminals (DiAntonio et al, 1999). Although all of the above experiments point to the importance of retrograde signals in presynaptic events, direct tests for a role of postsynaptic receptors in altering developmental acquisition of presynaptic release machinery have been hampered by the lack of ACh receptor (AChR) null animal model systems.…”
Section: Introductionmentioning
confidence: 99%
“…The change in mEJC amplitude without a change in mEJC frequency is supportive of a postsynaptic effect. Importantly, smaller mEJC amplitudes and faster mEJC decay times occur when B-Class GluRs are expressed exclusively, or when these receptors are present in greater relative abundance (DiAntonio et al, 1999;.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the synaptic functional changes likely result from this increase in B-class relative to A-class receptors, reflecting differences in A-class and B-class GluR properties. In particular, it has been shown that B-class receptors desensitize much more rapidly than A-class receptors based on analysis of currents in outside-out patches from GluRIIA and GluRIIB knockout animals (DiAntonio et al 1999). If B-class receptor desensitization is regulated through a calcium-dependent mechanism, this could explain the increased EJC amplitudes in lower calcium with no amplitude changes in higher calcium.…”
Section: B-class Glutamate Receptors Are Specifically Regulated By Thmentioning
confidence: 99%
See 1 more Smart Citation